Comparing COVID-19 in the antipodes: Insights from pandemic containment strategies on both sides of the Pacific. (September 2022) - Benita, Francisco; Fuentes, Luis; Guzmán, Luis A.; Martínez, Rafael; Carlos Muñoz, Juan; Neo, Harvey; Rodríguez-Leiva, Sebastian; Soza-Parra, Jaime
Highlights: Population density, housing crowding and poverty are associated to infections. Google Mobility Reports as promising source of reliable data for comparative studies. The cities' peripheries tend to concentrate the bulk of contagions. Abstract: That the COVID-19 pandemic is unprecedented in terms of its scale, spread and shocks can be evinced by the myriad of ever-changing responses cities all around the world have rolled out throughout the different waves of outbreaks. Although the threat is similar across the world, it took some time before its reach became global and the waves of outbreak are experienced by cities at different times. While this staggered spread imply that some cities might manage the virus better as they learn from the experiences of cities which had been amongst the earliest to face the virus, the reality is more complicated. In the early stages of the pandemic, the global consensus on the best way to contain the virus swiftly converged in the interlinked strategies of restricting the movement of people and minimizing their social contact. However, the effectiveness of these strategies differ greatly between cities. To that end, this study focuses on COVID-19 responses in two regions (Latin America and Southeast Asia) and examines the evolution of the first wave of COVID-19 outbreaks during 2020 in Singapore, Jakarta (Indonesia), Bogotá (Colombia) and Santiago (Chile). The study is based on a comparative approach and uses a variety of data sources, namely morphology, density, housing concentration, mobility, and governance in the four analyzed cities. The goal is to shed light on the response of city governments in these two different regions in terms of mobility restrictions in order to reduce the cases of new infections. The results show the relevance of urban policies and their territorial approaches, particularly in terms of mobility and public transport networks in the four cities.